STUDY OF PERFORMANCE TB SERVICES IN THE KALUGA REGION - I. S. Lapshina; V. A. Andreev; T. V. Myakisheva (Медицинский вестник Юга России, 2016)
Purpose: to examine the effectiveness of the TB control system in the Kaluga region in the modernization and optimization of health. Materials and methods: the medical records of the analysis of new TB cases. Results: the article shows that timely detection of tuberculosis in the Kaluga region at a low level. It was established nonhomogeneous quarterly detection of TB patients. The analysis of the effectiveness of the TB system in the Kaluga region. Summary: the results show weaknesses in the organization of detection and treatment of tuberculosis in the region.